PEMETAAN PENELITIAN BERBASIS PRODUK SEBAGAI BASIS PENENTUAN STRATEGI KOMUNIKASI SAINS - Saputro, Eko Prasetyo Nugroho; Dwiningrum, Siti Irene Astuti; Rosana, Dadan; Kumalasari, Dyah (Refleksi Edukatika : Jurnal Ilmiah Kependidikan, 2024)
This research aims to map the research products of Universitas Negeri Yogyakarta (UNY) lecturers from 2021 to 2023 as a basis for determining effective science communication strategies. It examines the research products generated through a grant scheme, emphasizing their downstream application and commercialization to achieve academic, economic, and social impact.The research employed a quantitative approach to organize research topics and a qualitative approach to describe research trends. Data were collected through documentation of research reports from faculty members of Yogyakarta State University (UNY), which were downloaded from the DRPM UNY system, totaling 1,845 documents, with 724 from 2023, 590 from 2022, and 531 from 2021. The collected data were then analyzed to identify the most frequently discussed research groups, keywords, and topics.The research results show variation in research groups over the years, with a dominance of innovation and learning groups in 2021, development and literacy groups in 2022, and analysis and learning model groups in 2023. The most frequently appearing keywords were "learning," "development," and "COVID-19" in 2021; "development," "learning," and "Yogyakarta" in 2022; and "development," "learning," and "model" in 2023. The most discussed topics included the COVID-19 pandemic, physical fitness, and the development of learning models. This research concludes that mapping research products can facilitate the grouping process, thereby aiding in the planning of effective science communication strategies. Such strategies are essential to ensure that research findings are accessible and understandable to the general public, thus increasing the appreciation and utilization of research outcomes.